Three-dimensional organotypic mouse brain slices to study Alzheimer’s disease pathologies: a review - Humpel, Christian (Frontiers in Dementia, 2025)
Alzheimer’s disease (AD) is a severe neurodegenerative brain disorder molecularly characterized by extracellular β-amyloid plaques, intraneuronal tau neurofibrillary tangles, cholinergic neuron death, neuroinflammation, vascular damage, and astroglial and microglial activation. AD is a complex disorder, with >99% of all cases being sporadic and typically occuring around the age of 65. Due to this intricate nature of the disorder, in vitro experiments have limitations; however, three-dimensional organotypic brain slices may offer the best alternative for studying the mechanisms involved in the progression of AD. This review provides an overview of how to study the general aspects of AD ex vivo, focusing on (a) β-amyloid plaques in brain slices, (b) tau pathology induced by chemical drugs, (c) cell death of cholinergic neurons and protection by nerve growth factor, (d) activation of astrocytes and microglia, and (e) vascular pathologies, including the role of platelets. Furthermore, we investigated (f) how microcontact printing on brain slices can be used to study the spread of β-amyloid and tau, and (g) how brain slices can help identify novel human AD biomarkers.